Effects of Daxx on γ-ray induced apoptosis of HeLa cells - TANG Shuangyang; DING Shuang; SHEN Haiyan; WU Hongrong; HU Yu; LIAO Yaqi; XIONG Yuling; LI Le (Fushe yanjiu yu fushe gongyi xuebao, 2021)
We studied the effects of overexpression of deathdomainassociated protein (Daxx) on cell apoptosis under γ-ray radiation. Further, we explored the relationship between Daxx and radiation-induced apoptosis and investigated the mechanism behind such apoptosis. Through transfection, cervicalcancer HeLa cells were divided into a control group, an empty plasmid-transfected negative group, and a Daxx-transfected group; the HeLa cells were irradiated with different doses of γ-rays using a cell irradiator. The expression of Daxx protein in cells was detected by Western blot. Cell proliferation was detected by MTT. The relative activity of caspase-8 in cells was detected by ELISA whereas the cell apoptosis was detected by flow cytometry. The results showed that the total number of cells decreased with the increase in absorbed dose, whereas the number of deformed cells increased. Furthermore, the degree of Daxx expression increased with the increase in absorbed dose. Comparing the cells of the Daxx-transfected group with those of the unirradiated control group, we observed statistically significant increments (p<0.01, p<0.05, p<0.05) in the rate of inhibition against cell proliferation, the A405 value, and rate of apoptosis. Hence, overexpression of Daxx promotes radiation-induced apoptosis by upregulating caspase-8 activity in the γ-ray irradiated cells.